2017
DOI: 10.1177/1471301217692905
|View full text |Cite
|
Sign up to set email alerts
|

Offering architects insights into experiences of living with dementia: A case study on orientation in space, time, and identity

Abstract: Due to memory loss, people with dementia are increasingly disorientated in space, time, and identity, which causes profound experiences of insecurity, anxiety, and homesickness. In the case study presented in this article, we explored how architecture can support people in coping with this challenge. We took a novel approach to offer architects insights into experiences of living with dementia. Starting from a critical realist and constructionist approach, we combined ethnographic techniques with an architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Other studies suggest that camouflaging exiting doors may reduce exiting behavior and door testing (Marquardt et al, 2014). Based on the findings of a study by Van Steenwinkel (2015) and the present study, however, using optical stickers or posters to distract residents' attention from the unit's possible exits seems to be ineffective and could moreover be questioned on ethical grounds. Similarly, one could argue that confining residents with dementia to a closed unit for their own safety is questionable.…”
Section: Thoughtful Design Of Physical and Visual Boundariescontrasting
confidence: 52%
See 1 more Smart Citation
“…Other studies suggest that camouflaging exiting doors may reduce exiting behavior and door testing (Marquardt et al, 2014). Based on the findings of a study by Van Steenwinkel (2015) and the present study, however, using optical stickers or posters to distract residents' attention from the unit's possible exits seems to be ineffective and could moreover be questioned on ethical grounds. Similarly, one could argue that confining residents with dementia to a closed unit for their own safety is questionable.…”
Section: Thoughtful Design Of Physical and Visual Boundariescontrasting
confidence: 52%
“…One of the architects' objectives was to offer what they call "structure in time, space, and social interaction" through the building's spatial organization, supportive color codes, and material choices. Spatial organization refers to how spatial entities are organized and which places and spatial relationships this organization creates (Van Steenwinkel, 2015, based on Unwin, 2009). This has implications for how the circulation space and other spaces in a building are arranged and interrelate.…”
Section: Contextmentioning
confidence: 99%
“…However, this can only be achievable in practice for caring relatives, who still share the same bedroom. Previous research indicated that space for 'escape' and privacy are preferable in living well with dementia (Gitlin, 2007; van Hoof & Kort, 2009;Van Steenwinkel, Van Audenhove, & Heylighen, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Architects typically need to turn to sources other than their own experience (or direct user involvement) to inform their design for people with dementia, but this is where they encounter difficulties (Van Steenwinkel, Van Audenhove and Heylighen 2012). Traditional research outcomes are difficult to apply, due to, e.g., the lack of spatial aspects in the content and the designer-unfriendly format (Van Steenwinkel 2015).…”
Section: Introductionmentioning
confidence: 99%